Algorithmic Authority and Public Trust: A Bibliometric Analysis of YouTube's Recommendation System in Shaping Islamic Religious Authority (2013-2023) - Samudra, Imam; Laini , Zakiyyah Wardatul; Juni yanti; Amin, Syukri; Fransiskus Novrianto Pakpahan (Cognoscere: Jurnal Komunikasi dan Media Pendidikan, 2024)
This study provides a comprehensive bibliometric analysis of the scholarly discourse on algorithmic authority and public trust concerning YouTube's recommendation system in shaping Islamic religious authority (2013-2023). Analyzing 677 Scopus-indexed documents from China, Indonesia, and Taiwan, this research employs co-citation and bibliographic coupling analyses to map the field's intellectual structure. The findings reveal a robust knowledge base anchored in studies of Islamic reformism, post-Islamism, and contemporary religious authority, while current research fronts explore the interplay of inspirational content, source credibility, and misinformation. The co-citation analysis identified key thematic clusters, including "Algorithmic Preachers," "The Digital Reformation of Indonesian Islam," and "The Pluralization of Islamic Discourse," demonstrating the field's theoretical depth. However, the study acknowledges limitations, including database dependency and the potential for artificial thematic convergence in algorithmic clustering. The bibliographic coupling revealed integrative clusters merging commercial and public health perspectives on user engagement, highlighting both the field's interdisciplinary nature and its conceptual challenges. Future research agendas propose methodological innovations in Islamic-specific algorithm auditing, theoretical expansion through integrating Islamic epistemology with algorithm studies, and ethical governance frameworks based on maqasid al-shariah. This analysis concludes that algorithmic authority constitutes a significant, evolving force in contemporary Islamic religious landscapes, necessitating continued critical investigation to navigate its implications for religious trust, authority, and community in increasingly digitized Muslim societies.